Functional Enhancers Shape Extrachromosomal Oncogene Amplifications - Morton, Andrew R; Dogan-Artun, Nergiz; Faber, Zachary J; MacLeod, Graham; Bartels, Cynthia F; Piazza, Megan S; Allan, Kevin C; Mack, Stephen C; Wang, Xiuxing; Gimple, Ryan C; Wu, Qiulian; Rubin, Brian P; et al. (Cell, 2019)
Non-coding regions amplified beyond oncogene borders have largely been ignored. Using a computational approach, we find signatures of significant co-amplification of non-coding DNA beyond the boundaries of amplified oncogenes across five cancer types. In glioblastoma, EGFR is preferentially co-amplified with its two endogenous enhancer elements active in the cell type of origin. These regulatory elements, their contacts, and their contribution to cell fitness are preserved on high-level circular extrachromosomal DNA amplifications. Interrogating the locus with a CRISPR interference screening approach reveals a diversity of additional elements that impact cell fitness. The pattern of fitness dependencies mirrors the rearrangement of regulatory elements and accompanying rewiring of the chromatin topology on the extrachromosomal amplicon. Our studies indicate that oncogene amplifications are shaped by regulatory dependencies in the non-coding genome.